Pengaruh mata kuliah perpajakan terhadap kesadaran wajib pajak: Studi kasus pada mahasiswa program studi Perbankan Syari’ah kelas A Universitas Islam Negeri Maulana Malik Ibrahim Malang - Cahyati, Dwi Nur; Kusuma, Muhammad Alfarizi; Akbar, Yodi Alrizky; Fitri, Anis Zakiyah; Fadilah, Siti Aisyah Nur (Maliki Interdisciplinary Journal, 2024)
The importance of teaching taxation courses, teaching methods the effectiveness and importance of the material on people's tax practices are factors that influence the results of this research. As a result of this research, there is a need to pay more attention than before to educational development programs that support increasing taxpayer understanding and awareness among students regarding the sharia banking curriculum. With a focus on A-level Islamic banking students at the Maulana Malik Ibrahim State Islamic University of Malang, this research aims to see how the taxation course has an impact on levels. awareness of their taxpayers. The research uses a questionnaire as a data collection tool. Students who have completed taxation courses are the respondents of this research. The research results show a positive and significant relationship between taking taxation classes and more student knowledge about tax obligations. Students who take taxation courses generally have a better understanding of tax obligations, rights and responsibilities as taxpayers, promising that this research will contribute to the development of tax education in higher education and provide a basis for further research regarding other components that may influence Taxpayer awareness in higher education, especially related to the related curriculum.